ChemInform Abstract: The Crystal Structure of Symplesite. Issue 34 (August 2015) - Runcevski, Tomce; Makreski, Petre; Dinnebier, Robert E.; Jovanovski, Gligor
Abstract The crystal structure of natural symplesite, Fe3(AsO4)2·8H2O is determined by high‐resolution powder XRD.